Functional Analysis of the TCR Binding Domain of Toxic Shock Syndrome Toxin-1 Predicts Further Diversity in MHC Class II/Superantigen/TCR Ternary Complexes - McCormick, John K. (2003)
Superantigens (SAGs) aberrantly alter immune system function through simultaneous interaction with lateral surfaces of MHC class II molecules on APCs and with particular variable regions of the TCR beta-chain (Vbeta). To further define the interface between the bacterial SAG toxic shock syndrome toxin-1 (TSST-1) and the TCR, we performed alanine scanning mutagenesis within the putative TCR binding region of TSST-1 along the central alpha helix adjacent to the N-terminal alpha helix and the beta7-beta9 loop as well as with two universally conserved SAG residues (Leu(137) and Tyr(144) in TSST-1). Mutants were analyzed for multiple functional activities, and various residues appeared to play minor or insignificant roles in the TCR interaction. The locations of six residues (Gly(16), Trp(116), Glu(132), His(135), Gln(136), and Gln(139)), each individually critical for functional activity as well as direct interaction with the human TCR Vbeta2.1-chain, indicate that the interface occurs in a novel region of the SAG molecule. Based on these data, a model of the MHC/TSST-1/TCR ternary complex predicts similarities seen with other characterized SAGs, although the CDR3 loop of Vbeta2.1 is probably involved in direct SAG-TCR molecular interactions, possibly contributing to the TCR Vbeta specificity of TSST-1.